2016
DOI: 10.1097/jhq.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Racial Disparities in Breast Cancer Survivors' Ratings of Quality Cancer Care

Abstract: Racial disparities in ratings of healthcare quality were diminished across several domains after controlling for psychosocial and healthcare factors. Strategies aimed at improving self-efficacy in women with higher levels of mistrust may improve patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…4547 Underlying this knowledge barrier may be concerns about genetic discrimination and a lack of trust in the medical system—a recurrent theme in the literature on African Americans. 48,49 A lack of provider referrals to genetic services as well as high costs and administrative barriers for these services have been shown to limit young African American breast cancer survivors’ participation in genetic counseling and testing. 50,51…”
Section: Discussionmentioning
confidence: 99%
“…4547 Underlying this knowledge barrier may be concerns about genetic discrimination and a lack of trust in the medical system—a recurrent theme in the literature on African Americans. 48,49 A lack of provider referrals to genetic services as well as high costs and administrative barriers for these services have been shown to limit young African American breast cancer survivors’ participation in genetic counseling and testing. 50,51…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Blacks report higher mistrust towards the medical establishment than their White counterparts [5][6][7]. Feelings of medical mistrust are more prevalent in Black breast cancer patients than White breast cancer patients and may contribute to existing disparities in treatment utilization [6,8]. Studies have shown that individuals who report greater medical mistrust also tend to have poorer physical and emotional well-being and quality of life [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…All three beliefs and attitudes have been found to predict less favorable patient perceptions of their physician because they relate to anticipation of bias (mistrust of physicians and past discrimination) and critical scrutiny (healthcare suspicion) (e.g., Hagiwara et al, 2013; Penner et al, 2009; Sheppard et al, 2016). We predicted that we would replicate these effects for mistrust and suspicion in oncology interactions on patient perceptions of the physician’s patient-centeredness during the interaction and trust for the physician.…”
Section: Introductionmentioning
confidence: 99%